Land institutions, investments, and income diversification: Pathways to economic development for Brazil’s quilombo communities - Bowser, William; Nelson, Carl H. (International Food Policy Research Institute, 2012)
Efforts to distribute land titles to low-income rural Afro-Brazilian communities, known as quilombos, have been disappointing despite the provision of ample government resources. Until now, research on the implications of Brazil s land reform policies has not considered quilombo communities in an economic context. The unique case of the quilombo communities provides an interesting context to advance the understanding of the role of land titles in rural income generation. The impact of land tenure security in the cycle of assets, activities, and income is explored to identify the importance of institutions for land dependent agricultural enterprises. We find evidence of land titles contributing to desirable welfare outcomes through their impact on production and investment behavior. Income diversity from various production activities is found to positively contribute to higher income levels, particularly for producers earning more than the minimum wage, once conditioned on secure land rights and productive investments.